2019
DOI: 10.1242/jcs.232249
|View full text |Cite
|
Sign up to set email alerts
|

Proximity-dependent biotinylation mediated by TurboID to identify protein–protein interaction networks in yeast

Abstract: The use of proximity-dependent biotinylation assays coupled to mass spectrometry (PDB-MS) has changed the field of protein-protein interaction studies. However, despite the recurrent and successful use of BioID-based protein-protein interactions screening in mammalian cells, the implementation of PDB-MS in yeast has not been effective. Here, we report a simple and rapid approach in yeast to effectively screen for proximal and interacting proteins in their natural cellular environment by using TurboID, a recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 43 publications
4
66
0
Order By: Relevance
“…Furthermore, we found that the biotinylated proteins had similar distribution patterns to the wild type, or disrupted cytoophidia, which suggested that the proximate proteins of CTPS-TbID/CTPS H355A -TbID were easily biotinylated ( Fig 3C). In the absence of exogenous biotin, some weak labelling signals were also detected by streptavidin-cy3 ( Fig 3C), which was expected because TbID has great efficiency and consumes endogenous biotin in cells in order to function, as was reported in previous studies (Branon et al, 2018;Larochelle et al, 2019).…”
Section: Biotinylation Of Cytoophidia Enabled By Turboidsupporting
confidence: 80%
See 2 more Smart Citations
“…Furthermore, we found that the biotinylated proteins had similar distribution patterns to the wild type, or disrupted cytoophidia, which suggested that the proximate proteins of CTPS-TbID/CTPS H355A -TbID were easily biotinylated ( Fig 3C). In the absence of exogenous biotin, some weak labelling signals were also detected by streptavidin-cy3 ( Fig 3C), which was expected because TbID has great efficiency and consumes endogenous biotin in cells in order to function, as was reported in previous studies (Branon et al, 2018;Larochelle et al, 2019).…”
Section: Biotinylation Of Cytoophidia Enabled By Turboidsupporting
confidence: 80%
“…Then, we analyzed the biotinylated proteins adjacent to CTPS-TbID or CTPS H355A -TbID by hierarchical clustering, and our results revealed the differences among the proteome between normal CTPS cytoophidium and disrupted cytoophidium groups (Fig 4B). To assess the relative abundance of the characterized proteins, we analyzed MS/MS counts plotted against the protein sequence coverage (percentage of amino acid of a protein characterized by MS) by calculating the counts of all peptides matching to a specific protein (Larochelle et al, 2019;Schwanhausser et al, 2011). In addition to CTP synthase, another two known CTPS-interacting proteins (awd, ras) were found in our assay, and, as expected, CTPsyn was determined as a top hit ( Fig 4C).…”
Section: Turboid-mediated Ctps Cytoophidium Proximate Proteomementioning
confidence: 62%
See 1 more Smart Citation
“…However, recent studies showed that this time might be adapted depending on the organism studied. While 10 min is sufficient in mammalian cells, TurboID‐mediated biotinylation requires about 30 min to 3 h in yeast, 4 h in flies, 4 h to several days in worms, and 12 h in plants . Optimization of the TurboID labeling time should therefore be done for each organism, especially to prevent toxicity via chronic endogenous biotinylation or endogenous biotin consumption due to the high activity of these enzymes …”
Section: What Is the Best Approach (For You)?mentioning
confidence: 99%
“…These elicitors are termed either microbe-associated molecular patterns (MAMPs) or pathogen-associated molecular patterns (PAMPs). Since these terms are frequently used interchangeably, we will maintain the broader term MAMP [ 1 ]. MAMPs are detected by pattern recognition receptors (PRRs) that induce various antimicrobial and immune responses to eliminate encroaching infective agents, referred to as MAMP-triggered immunity (MTI) [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%